Influence of School Principal's Attributes and 21st-Century Leadership Skills on Teachers’ Performance - De Castro, Gerly B.; Jimenez, Edward C. (Journal of Humanities and Social Sciences (JHASS), 2022)
This study aimed to determine the influence of school principals' attributes and 21st Century Leadership skills on teachers' performance. The study is as follows. The teachers in the northern part of the National Capital Region are female, teacher I position, have rendered 5 – 14 years of service, and pursued higher studies after college. The teacher's attribute that influences the teacher's job performance is openness. The School Head always comes up with new ideas. They have an active imagination; creative is a deep thinker and values artistic experiences. He is dependable, organized, and persevering, which means they will accomplish their professional goals. The 21st Century Leadership Skills of the school principal that dominantly influence the teacher's job performance is the communication skills. The school head is approachable, gives clear and accurate information and instructions both in oral and written communication, discusses issues and feedback in school, listens to and appreciates teachers' ideas and suggestions, and communicates with his/her staff regularly. The teachers' performance is very satisfactory as perceived by their school heads during 2019 – 2020. There is a significant difference in the attributes, 21st-century leadership skills of school heads and teachers, job performance when grouped according to schools division office, and years in service. Significant relationships exist between the principals' attributes, 21st-century leadership skills, and teachers' job performance. Personal attributes and 21st-century leadership skills of the school principals significantly influence the teachers' job performance